Use of tire rubber in dense asphalt mixture for infrastructure projects - Botasso, Gerardo (2025)
The present work is raised from the utilization perspective of tire waste that is out of use. It is well known the problem of its deposits in different countries and the great demand of these as a waste, the lack of legislation of rubbish dumps, and the proliferation of diseases and insects that are generated in them. Taking advantage of the new technologies in asphalt emulsion production machinery, it's how we saw the need of a study of the incorporation of tire dust into asphalt emulsions.  From the LEMAC, Center of Road Researches, the proposal of using tire dust produced by Molicaucho was boosted. At the same time, the process of making the rubber dispersion in the REPSOL-YPF refinery of Ensenada was established, to make a dense asphalt mix for its use as a bearing layer, not before checking out its efficacy.  This is how the main characteristics of the base asphalt and the rubber were studied, as well as the dispersions of both of them, the arids to make the dense mix, the production in an asphalt-rubber industrial plant, its placing in the building site with an experimental section in the city of La Plata and the subsequent verification of the mix through the extraction of samples.